Justification of the parameters affecting the maneuverability of a four-wheeled tractor - Kambarov Bakhtiyor; Ashirov Vosit; Ravshanov Shavkat; Mirzayev Najmiddin (EPJ Web of Conferences)
This paper presents the development and experimental design of an enhanced front driving axle for a new universal cotton cultivating tractor, designated as 4K4. The innovative axle design significantly increases the tractor's agrotechnical clearance, enabling improved performance in cotton cultivation. The 4K4 propulsion scheme enhances the tractor's traction capabilities by 15-18%, allowing it to efficiently operate machinery for cotton production across four or more rows simultaneously. A key advantage of the 4K4 configuration is the reduced vertical load on individual wheels, which contributes to superior directional stability and safer lateral static stability of the Machine Tractor Unit. This design feature not only optimizes the tractor's performance in cotton fields but also extends its utility, enabling year-round application in both transportation and various field operations. The research highlights the potential of this advanced tractor design to significantly improve efficiency and versatility in cotton cultivation, addressing the specific needs of the industry while offering broader agricultural applications.